Suicidal Risk Factors of Recurrent Major Depression in Han Chinese Women - Zhu, Yuzhang (Public Library of Science, 2013)
The relationship between suicidality and major depression is complex. Socio- demography, clinical features, comorbidity, clinical symptoms, and stressful life events are important factors influencing suicide in major depression, but these are not well defined. Thus, the aim of the present study was to assess the associations between the above-mentioned factors and suicide ideation, suicide plan, and suicide attempt in 6008 Han Chinese women with recurrent major depression (MD). Patients with any suicidality had significantly more MD symptoms, a significantly greater number of stressful life events, a positive family history of MD, a greater number of episodes, a significant experience of melancholia, and earlier age of onset. Comorbidity with dysthymia, generalized anxiety disorder (GAD), social phobia, and animal phobia was seen in suicidal patients. The present findings indicate that specific factors act to increase the likelihood of suicide in MD. Our results may help improve the clinical assessment of suicide risk in depressed patients, especially for women.